2023
DOI: 10.3390/children10020246
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Admissions of Children with Chest Pain before and during COVID-19 Pandemic

Abstract: Objectives: We compared the number of accesses, causes, and instrumental evaluations of chest pain in children between the pre-COVID-19 era and the COVID-19 period and analyzed the assessment performed in children with chest pain, highlighting unnecessary examinations. Methods: We enrolled children with chest pain admitted to our emergency department between January 2019 and May 2021. We collected demographic and clinical characteristics and findings on physical examinations, laboratory tests, and diagnostic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Psychogenic chest pain is also a common cause among children and adolescents. According to previous studies, it accounts for about 5.1-83.6% of all cases in this group [1,2,9,14,[17][18][19]. Recent studies have found that psychogenic chest pain in children and adolescents may exceed 20.0% [1,14,17,19], with some studies indicating as high as 83.6% [17].…”
Section: Etiology Of Chest Pain In Children and Adolescentsmentioning
confidence: 91%
See 4 more Smart Citations
“…Psychogenic chest pain is also a common cause among children and adolescents. According to previous studies, it accounts for about 5.1-83.6% of all cases in this group [1,2,9,14,[17][18][19]. Recent studies have found that psychogenic chest pain in children and adolescents may exceed 20.0% [1,14,17,19], with some studies indicating as high as 83.6% [17].…”
Section: Etiology Of Chest Pain In Children and Adolescentsmentioning
confidence: 91%
“…Chest pain in children and adolescents could be divided into the following etiologies: musculoskeletal, idiopathic, pulmonary, gastrointestinal, psychogenic, cardiac, or miscellaneous causes [ 1 , 2 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Due to varying classifications of the causes of chest pain in different articles and the lack of uniformity in diagnostic definitions among these articles, the exact proportion of chest pain in children and adolescents varies from study to study.…”
Section: Etiology Of Chest Pain In Children and Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations